Professional Pressures in a sample of teachers of the first cycle of basic education Field study in Lattakia - Barakat, Gassan; Ali, Rania; Nasser, Abeer (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aims to identify the level of professional pressures of teachers, and to know the difference between the members of the research sample in professional pressures according to the sex variable. To acheive the objectives of the research, the professional pressures was used by the researcher. The researcher studied his psychometric characteristics. In order to judge the veracity of the scale, it was presented to a group of (14) specialized arbitrators in the Faculty of Education at the Universities of Tishreen and AL_Baath, In order to study its stability, it was applied to a survery sample from outside the research. The number of teachers (males and females) from the basic education stage in Lattakia was (40). The stability of the scale was calculated by the Cronbach_Alpha method, where the value of the Cronbach _Alpha coefficient of the scale was (a=o.855). After verification of validity and reliability, the scale was applied to a sample of 688 teachers, including 370 teachers (females) and 318 teachers (males). The descriptive approach was used. The research concluded that the level of professional pressures in a sample of teachers in Lattakia is at the intermediate level. There is no statistically significant difference between the average grade of teachers (males) and the average grade of teachers (females) on the scale of professional pressures.